1996
DOI: 10.1093/ndt/11.3.468
|View full text |Cite
|
Sign up to set email alerts
|

Pneumococcal vaccine in children and young adults with chronic renal disease

Abstract: The currently available vaccine is without major side-effects and effective in producing a significant immune response. Antibody levels should be monitored in vaccinated patients with chronic renal diseases considering the rapid decline as early as 6 months after vaccination. Evaluation of the efficacy of revaccination in these patients requires further investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 24 publications
2
44
0
1
Order By: Relevance
“…In contrast, children with steroid-resistant nephrotic syndrome have been observed to have significantly lower levels of anti-pneumococcal antibodies to numerous specific capsular types as compared with healthy children (41). It is interesting that revaccination of children and young adults who have kidney disease (both CKD and ESRD) who lose protective titers 1 yr after initial vaccination has been associated with a lower response rate and more rapid loss of protective antibody titers as compared with the initial vaccination (42).…”
Section: Vaccinationmentioning
confidence: 99%
“…In contrast, children with steroid-resistant nephrotic syndrome have been observed to have significantly lower levels of anti-pneumococcal antibodies to numerous specific capsular types as compared with healthy children (41). It is interesting that revaccination of children and young adults who have kidney disease (both CKD and ESRD) who lose protective titers 1 yr after initial vaccination has been associated with a lower response rate and more rapid loss of protective antibody titers as compared with the initial vaccination (42).…”
Section: Vaccinationmentioning
confidence: 99%
“…[5] In addition, it has been demonstrated that protection against diphtheria and the immune response to Td vaccine in hemodialysis (HD) patients is poor (i.e., a seroconversion rate of 37%). [16,17] It is also noteworthy to mention that the response to tetanus and diphtheria vaccinations is highly related (p < 0.04). [1] Although several studies have focused on the protection of HD patients against infections by vaccination, no guidelines are yet available for preventive care in patients with CKD, including the use of vaccines such as the Td booster vaccine.…”
Section: Introductionmentioning
confidence: 97%
“…However, hyporesponsiveness to several vaccines has been described in children with CKD (9)(10)(11)(12)(13)(14)(15)(16). In this study, we examine the immunogenicity of the quadrivalent HPV vaccine in girls with CKD, ESRD, or kidney transplants.…”
Section: Introductionmentioning
confidence: 99%